Load Flow Analysis And Planning Of Radial Distribution Systems- A New Approach Of Load Modelling, Load Forecasting And Feeder Planning - Chaturvedi, Ashvini (2007)
Work presented in this theses deals with the performance of RDS with load uncertainty, planning of substation and feeder arrangement considering anticipated future load growth.